2009
DOI: 10.1001/archoto.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of the Multiple-Frequency 80-Hz Auditory Steady-State Response in Adults With Normal Hearing and Hearing Loss

Abstract: In adults, the multiple-frequency 80-Hz ASSR technique can be used to determine the degree and configuration of hearing loss. Although air-conduction ASSR thresholds accurately predicted behavioral thresholds in CHL, future research with bone-conduction ASSRs is necessary to establish the type of hearing loss. Furthermore, the applicability of these findings still needs to be confirmed for infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
2
18
2
8
Order By: Relevance
“…9 No PEAEE os resultados são apresentados na forma de um audiograma eletrofisiológico. 9 Eles podem variar dependendo do número / tipo de estímulo e modulação apresentados, da idade e tipo de população recrutada, nível de relaxamento, estado de consciência, artefatos elétricos, alterações 19 Luiz (2016) encontrou valores entre -0,3 e 12 dB para o grupo com audição normal, e entre -9 e 2 dB para o grupo com perda auditiva de grau moderado a moderadamente severo. 15 Rodrigues e Lewis (2010), comparando PEAEE e VRA (audiometria de reforço visual) em crianças com perdas auditivas cocleares, encontraram diferenças de -1,7/1,5/-0,1/-4,5 dB, indicando com os valores negativos que, em algum momento, o PEAEE apresentou melhores resultados auditivos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…9 No PEAEE os resultados são apresentados na forma de um audiograma eletrofisiológico. 9 Eles podem variar dependendo do número / tipo de estímulo e modulação apresentados, da idade e tipo de população recrutada, nível de relaxamento, estado de consciência, artefatos elétricos, alterações 19 Luiz (2016) encontrou valores entre -0,3 e 12 dB para o grupo com audição normal, e entre -9 e 2 dB para o grupo com perda auditiva de grau moderado a moderadamente severo. 15 Rodrigues e Lewis (2010), comparando PEAEE e VRA (audiometria de reforço visual) em crianças com perdas auditivas cocleares, encontraram diferenças de -1,7/1,5/-0,1/-4,5 dB, indicando com os valores negativos que, em algum momento, o PEAEE apresentou melhores resultados auditivos.…”
Section: Discussionunclassified
“…20 Diversos autores relatam que pode ocorrer uma maior diferença entre o limiar tonal e por PEAEE nas frequências graves. 9,15,16,19,21,22 A justificativa levantada seria o maior tempo que o estímulo sonoro leva para percorrer toda a cóclea (tonotopia coclear), além do efeito de mascaramento que o ruído ambiental pode causar 11,18,19 Acrescente-se a tudo isso o fato da amplitude de resposta ser menor nessa região e a localização dos artefatos elétricos estar justamente dentro do intervalo dessa frequência e das adjacentes de modulação. 22 Hosseinabadi e Jafarzadeh (2015) referem que nesta frequência pode haver menor sincronização neural.…”
unclassified
“…The click is the usual stimuli for ABR testing but its thresholds reflect broad and uncertain frequency region (3) correlate with behavioral thresholds of 1000 to 4000 Hz. Although tone burst stimuli have better frequency specificity, the interpretation of their waves and test time depend on the experience of the examiner (4, 5), especially at lower frequencies and in cases with hearing loss. In addition, ABR has limitations on presentation of high-intensity stimuli and the determining of its waves relies on examiner’s judgment; hence, it is not a completely objective test.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that using tone-ABR and a higher mean age of subjects (the mean age of the patients was 18.3 months in that study) might be responsible for this difference. In addition, another study reported a cut-off value of 30 dB for all frequencies in adults [27] . The differences between studies may be related to the poorer detection of the ASSR responses in patients with mild hearing loss [28] .…”
mentioning
confidence: 99%